Induction of interleukin‐1β by activated microglia is a prerequisite for immunologically induced fatigue. (5th July 2014) - Ifuku, Masataka; Hossain, Shamim M.; Noda, Mami; Katafuchi, Toshihiko
Abstract We previously reported that an intraperitoneal (i.p.) injection of synthetic double‐stranded RNA, polyriboinosinic:polyribocytidylic acid (poly‐I:C), produced prolonged fatigue in rats, which might serve as a model for chronic fatigue syndrome. The poly‐I:C‐induced fatigue was associated with serotonin transporter (5‐HTT) overexpression in the prefrontal cortex (PFC), a brain region that has been suggested to be critical for fatigue sensation. In the present study, we demonstrated that microglial activation in the PFC was important for poly‐I:C‐induced fatigue in rats, as pretreatment with minocycline, an inhibitor of microglial activation, prevented the decrease in running wheel activity. Poly‐I:C injection increased the microglial interleukin (IL)‐1β expression in the PFC. An intracerebroventricular (i.c.v.) injection of IL‐1β neutralising antibody limited the poly‐I:C‐induced decrease in activity, whereas IL‐1β (i.c.v.) reduced the activity in a dose‐dependent manner. 5‐HTT expression was enhanced by IL‐1β in primary cultured astrocytes but not in microglia. Poly‐I:C injection (i.p.) caused an increase in 5‐HTT expression in astrocytes in the PFC of the rat, which was inhibited by pretreatment with minocycline (i.p.) and rat recombinant IL‐1 receptor antagonist (i.c.v.). Poly‐I:C injection (i.p.) led to a breakdown of the blood–brain barrier and enhanced Toll‐like receptor 3 signaling in the brain. Furthermore, direct application of poly‐I:C enhanced IL‐1β expression in primary microglia. We therefore propose that poly‐I:C‐induced microglial activation, which may be at least partly caused by a direct action of poly‐I:C, enhances IL‐1β expression. Then, IL‐1β induces 5‐HTT expression in astrocytes, resulting in the immunologically induced fatigue.